Conceptual Framework Of Decentralization Policy : A Case Of Local Government In Thailand - Thuanthong Krutchon (FISIP UNHAS, 2015)
Abstract : This paper has three purposes. First, it aims to critically review the conceptual framework of decentralization policy of local government in Thailand. According to the scholars’ perspective, the term “local government” is viewed as a self-governance. Thus, this paper presents a brief concept of Thai local government context consisting of general form –PAO, Municipality, SAO and special form-BMA and City of Pattaya. Second, this paper discusses decentralization policy in Thailand. In doing so, five major taxonomies of authority have been portrayed on governance and thought, infrastructure, economic, commerce and finance, society and quality of life, and natural resources and environment. Moreover, Two case studies are reviewed to illustrate decentralization policy in Thai local government. Finally, this paper gives the suggestion for future direction of decentralization policy in Thailand. Keywords : Decentralization policy, Authority, Thai Local GovernmentAbstrak : Makalah ini memiliki tiga tujuan. Pertama, bertujuan untuk meninjau secara kritis kerangka kebijakan konseptual desentralisasi pemerintah daerah di Thailand. Menurut perspektif para cendekiawan, istilah “pemerintah daerah” dipandang sebagai pemerintahan mandiri. Dengan demikian, makalah ini menyajikan konsep singkat Thailand dengan konteks pemerintah daerah yang terdiri dari bentuk umum -PAO, Municipality, SAO dan khusus bentuk BMA dan Kota Pattaya. Kedua, tulisan ini membahas kebijakan desentralisasi di Thailand. Dengan demikian, lima taksonomi utama otoritas telah digambarkan di pemerintahan dan pikiran, infrastruktur, ekonomi, perdagangan dan keuangan, masyarakat dan kualitas hidup, dan sumber daya alam dan lingkungan hidup. Selain itu, dua studi kasus Ulasan untuk menggambarkan kebijakan desentralisasi di pemerintah daerah Thailand. Akhirnya, tulisan ini memberikan saran untuk arah masa depan kebijakan desentralisasi di Thailand. Kata kunci : kebijakan Desentralisasi, Kewenangan, Pemerintah Daerah Thailand